An assessment of fatigability following nerve transfer to reinnervate elbow flexor muscles. (July 2019) - Wilcox, M.; Brown, H.; Johnson, K.; Sinisi, M.; Quick, T. J.
Abstract : Aims: Improvements in the evaluation of outcomes following peripheral nerve injury are needed. Recent studies have identified muscle fatigue as an inevitable consequence of muscle reinnervation. This study aimed to quantify and characterize muscle fatigue within a standardized surgical model of muscle reinnervation. Patients and Methods: This retrospective cohort study included 12 patients who underwent Oberlin nerve transfer in an attempt to restore flexion of the elbow following brachial plexus injury. There were ten men and two women with a mean age of 45.5 years (27 to 69). The mean follow-up was 58 months (28 to 100). Repeated and sustained isometric contractions of the elbow flexors were used to assess fatigability of reinnervated muscle. The strength of elbow flexion was measured using a static dynamometer (KgF) and surface electromyography (sEMG). Recordings were used to quantify and characterize fatigability of the reinnervated elbow flexor muscles compared with the uninjured contralateral side. Results: The mean peak force of elbow flexion was 7.88 KgF (sd 3.80) compared with 20.65 KgF (sd 6.88) on the contralateral side (p < 0.001). Reinnervated elbow flexor muscles (biceps brachialis) showed sEMG evidence of fatigue earlier than normal controls with sustained (60-second) isometric contraction. Reinnervated elbow flexor muscles also showed a trend towards a faster twitch muscle fibre type. Conclusion: The assessment of motor outcomes must involve more than peak force alone. Reinnervated muscle shows a shift towards fast twitch fibres following reinnervation with an earlier onset of fatigue. Our findings suggest that fatigue is a clinically relevant characteristic of reinnervated muscle. Adoption of these metrics into clinical practice and the assessment of outcome could allow a more meaningful comparison to be made between differing forms of treatment and encourage advances in the management of motor recovery following nerve transfer. Cite this article: Bone Joint J 2019;101-B:867–871.